FROM THE MINIMUM CURRICULUM TO THE PPC: THE TRAJECTORY OF THE LIBRARY SCIENCE COURSE AT UNB - Caribé, Rita de Cássia do Vale; de Brito, Marcílio (Seven Editora, 2025)
This article presents a historical analysis of the development process of the Pedagogical Course Project (PPC) for the Library Science program at the Faculty of Information Science (FCI) of the University of Brasília (UnB). Based on a qualitative and descriptive approach, documentary sources such as legislation, resolutions, and specialized literature were examined. The study highlights that, despite the mandatory implementation of the PPC since the 1996 National Education Guidelines and Framework Law (LDB) and the curricular guidelines established in 2002, the Library Science program at UnB only began its formulation process in 2019. Periods of innovation and stagnation were identified throughout the curriculum’s evolution, emphasizing challenges in preserving institutional memory and systematizing historical course information. It is concluded that the historical documentation of this process is essential for future curriculum reforms and for consolidating the academic identity of the program. DOI: https://doi.org/10.56238/sevened2025.038-022